2016
DOI: 10.1177/0143624416652182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of elevator group control algorithms using a three-element new paradigm

Abstract: This paper presents a new paradigm for assessing the effectiveness of up-peak elevator group control algorithms. The new paradigm can be very effective in providing a mechanism for objectively assessing and comparing elevator group control algorithms. It is built around three essential components: idealised optimal benchmarks; random scenario testing; and progressive introduction of reality. An idealised optimal benchmark is the starting point for calculating an analytical upper bound for the performance of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Correspondingly, all uncertain situations caused by single uncertain factor and t-way interactions (see Definition 7) among several uncertain factors in uncertain factor set π‘ˆ can be represented by set π‘ˆ 𝑆 = {𝑒𝑠 π‘œ |π‘œ = 1, 2, ..., 𝑁 𝑆 }, where 𝑒𝑠 π‘œ is the π‘œth uncertain situation caused by π‘ˆ , 𝑁 𝑆 is the number of uncertain situations, there are 𝑁 𝑆 = 𝑒𝑛 𝑑 =1 𝐢 𝑑 𝑒𝑛 = 2 𝑒𝑛 βˆ’ 1 uncertain situations in total, which can be simulated by 2 𝑒𝑛 βˆ’ 1 types of uncertain traffic profiles (see Definition 6). For example, to investigate uncertain factor set π‘ˆ with three uncertain factors {𝑒 1 = Mass (M), 𝑒 2 = Loading Time (L), 𝑒 3 = Unloading Time (U )}, the total number of uncertain situations caused by π‘ˆ is 7, of which 3 (𝐢 1 3 ) are caused by single uncertain factor {𝑒𝑠 1 = 𝑒𝑠𝑀, 𝑒𝑠 2 = 𝑒𝑠𝐿, 𝑒𝑠 3 = π‘’π‘ π‘ˆ }, 3 (𝐢 2 3 ) are caused by 2-way interactions {𝑒𝑠 4 = 𝑒𝑠𝑀 βˆ’ 𝐿, 𝑒𝑠 5 = 𝑒𝑠𝑀 βˆ’ π‘ˆ , 𝑒𝑠 6 = 𝑒𝑠𝐿 βˆ’ π‘ˆ } and 1 is (𝐢 3 3 ) caused by 3-way interactions {𝑒𝑠 7 = 𝑒𝑠𝑀 βˆ’ 𝐿 βˆ’ π‘ˆ }. Studying interactions among uncertain factors is important since effects (e.g., degraded QoS) might only be visible when a dispatcher faces uncertainties from a less number of uncertain factors simultaneously.…”
Section: Generation Of Uncertain Traffic Profiles (mentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, all uncertain situations caused by single uncertain factor and t-way interactions (see Definition 7) among several uncertain factors in uncertain factor set π‘ˆ can be represented by set π‘ˆ 𝑆 = {𝑒𝑠 π‘œ |π‘œ = 1, 2, ..., 𝑁 𝑆 }, where 𝑒𝑠 π‘œ is the π‘œth uncertain situation caused by π‘ˆ , 𝑁 𝑆 is the number of uncertain situations, there are 𝑁 𝑆 = 𝑒𝑛 𝑑 =1 𝐢 𝑑 𝑒𝑛 = 2 𝑒𝑛 βˆ’ 1 uncertain situations in total, which can be simulated by 2 𝑒𝑛 βˆ’ 1 types of uncertain traffic profiles (see Definition 6). For example, to investigate uncertain factor set π‘ˆ with three uncertain factors {𝑒 1 = Mass (M), 𝑒 2 = Loading Time (L), 𝑒 3 = Unloading Time (U )}, the total number of uncertain situations caused by π‘ˆ is 7, of which 3 (𝐢 1 3 ) are caused by single uncertain factor {𝑒𝑠 1 = 𝑒𝑠𝑀, 𝑒𝑠 2 = 𝑒𝑠𝐿, 𝑒𝑠 3 = π‘’π‘ π‘ˆ }, 3 (𝐢 2 3 ) are caused by 2-way interactions {𝑒𝑠 4 = 𝑒𝑠𝑀 βˆ’ 𝐿, 𝑒𝑠 5 = 𝑒𝑠𝑀 βˆ’ π‘ˆ , 𝑒𝑠 6 = 𝑒𝑠𝐿 βˆ’ π‘ˆ } and 1 is (𝐢 3 3 ) caused by 3-way interactions {𝑒𝑠 7 = 𝑒𝑠𝑀 βˆ’ 𝐿 βˆ’ π‘ˆ }. Studying interactions among uncertain factors is important since effects (e.g., degraded QoS) might only be visible when a dispatcher faces uncertainties from a less number of uncertain factors simultaneously.…”
Section: Generation Of Uncertain Traffic Profiles (mentioning
confidence: 99%
“…They increased the current from 1.5A to 9.9A and observed that the maximum air-cooling capacity can be obtained at 9.4A. Al-Sharif et al [3] proposed a paradigm with three components for testing the performance of elevator group control algorithms using idealized benchmarks, random scenario testing, and gradually making scenarios more realistic. Wang et al [51] tested the seismic performance of a functional traction elevator in a reinforced concrete building under earthquake.…”
Section: Testing Elevator Systemsmentioning
confidence: 99%
“…Due to the reduction in the round trip time caused by the effects in 2 and 3 above, a reduction in the number of passengers boarding the car results (leading to smaller car loading); or more passengers can be taken into the elevator car (leading to an increase in the handling capacity). Algorithms that attempt to minimize the number of stops and the highest reversal floor are described in Al-Sharif et al, 24,25 and Al-Shrarif. 26…”
Section: The Effects Of Sectoringmentioning
confidence: 99%